On the effectiveness of ventilation to mitigate the damage of spherical membrane vessels subjected to internal detonations - Hernandez, F.; Zhang, Xihong; Hao, Hong (2020)
This article conducts a comparative study on the effectiveness of ventilation to mitigate blasting effects on spherical chambers subjected to internal detonations of high explosives through finite element analysis using the software package AUTODYN. Numerical simulations show that ventilation is ineffective in mitigating the damage of spherical chambers subjected to internal high explosives explosions because the chamber response is mainly described by high-frequency membrane modes. Openings do not reduce the chamber response despite they can reduce the blast overpressure after the chamber reaches its peak response. Worse still, openings lead to stress concentration, which weakens the structure. Therefore, small openings may reduce the capacity of the chamber to resist internal explosions. In addition, because large shock waves impose the chamber to respond to a reverberation frequency associated with the re-reflected shock wave pulses, secondary re-reflected shock waves can govern the chamber response, and plastic/elastic resonance can occur to the chamber. Simulations show that the time lag between the first and the second shock wave ranges from 3 to 7 times the arrival time of the first shock wave, implying that the current simplified design approach should be revised. The response of chambers subjected to eccentric detonations is also studied. Results show that due to asymmetric explosions, other membrane modes may govern the chamber response and causes localized damage, implying that ventilation is also ineffective to mitigate the damage of spherical chambers subjected to eccentric detonations.